Avaliação de recrutamento de células da resposta imune inata por BCG Moreau na ausência de citocinas IL-17 e IL-22 - Resende, Danilo Pires de (2015)
Tuberculosis is an infectious disease responsible for millions of deaths every year. BCG (Bacille Calmette-Guérin) is the only licensed vaccine for the prevention of human tuberculosis (TB). Early production of IL-17 and IL-22 as induced by BCG is important for protective memory cells formation in TB. In this context, we evaluated the role of these cytokines in the recruitment and activation of cells of the innate immunity induced by BCG vaccine. C57BL/6, IL22 _ /_ and IL17_ /_ mice were used. Cells obtained after peritoneal lavage were evaluated by flow cytometry and citospin 24 hours, 2, 3, 5 and 7 days after infection with BCG, intraperitoneally (1x106/ml). The macrophages recruitment (F4/80 + CD11+) to the peritoneum was similar for all animals, but in IL17_ /_ mice, these cells expressed more MHCII molecules. Neutrophils (Gr1+), initially presented higher percentage in IL17_/_ and IL22_/_ mice compared with C57BL/6 (50.9 ± 5.4, 31.7 ± 1.7). These cells where more activated (Gr1+CD11b+) in the IL17_/_ mice at 5 days post inoculation. NK cells (NK1.1+) was recruited in C57BL/6, mice whereas few NK cells migrated to the peritoneum in IL22_ /_ and IL17_/_ mice, two days after inoculation. Again, these cells were also more activated in IL17_/_ than in other animals (NK1.1+ CD11b+). In summary, intraperitoneal immunization with BCG recruit macrophages, neutrophils and NK cells into the peritoneum. In the absence of IL17 these cells are more activated than in the other mice, indicating a higher activated profile, although these cells were reduced.